Organization of the training process of short distance runners at the stage of initial sports specialization - Huaxing, Z.; Zinovenko, K. A.; Vrublevskiy, E. P. - (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the main aspects of the organization of the training process of sprint runners in the People's Republic of China and the Republic of Belarus at the stage of initial sports specialization.